Web-Based Language Translator to Facilitate Communication between International Students and Non-Academic Staff - Abdulaziz, Wasim Meftah (2010)
The birth of Web-Based Language Translator in the computer world has brought harmony among people regardless of variation in their languages. This project work focuses on the development of a Web-Based Language Translator that translates Malay language into English language, and vise-versa to facilitate a smooth communication between the non-academic staffs and the international students of the University Utara Malaysia. Also, we discussed related works on the language translation in accordance to Web-Based Application. We also describe five unique systematic ways to achieve our research objectives. In addition, the project describes system prototype development adopted for this research, its functional requirements, use case diagram and use case specification, sequence diagram, collaboration diagram and the class diagram. The evaluation of the techniques used to show the level of usefulness and operability of the system is also discussed. Consequently, the users of the prototype found it flexible, consistent with helpful and effective user guidance through the software analysis and descriptive analysis.